Functional characterization of colon cancer-associated mutations in ADAM17: Modifications in the pro-domain interfere with trafficking and maturation - Pavlenko, Egor; Cabron, Anne-Sophie; Arnold, Philipp; Dobert, Jan Philipp; Rose-John, Stefan; Zunke, Friederike (International Journal of Molecular Sciences, 2019)
Colorectal cancer is one of the most commonly diagnosed malignancies in the Western world and is associated with elevated expression and activity of epidermal growth factor receptors (EGF-R). The metalloproteinase ADAM17 is involved in EGF-R activation by processing EGF-R ligands from membrane-bound pro-ligands. Underlining the link between colon cancer and ADAM17, genetic intestinal cancer models in ADAM17-deficient mice show a reduced tumor burden. In this study, we characterize point mutations within the ADAM17 gene found in the tissue of colon cancer patients. In order to shed light on the role of ADAM17 in cancer development, as well as into the mechanisms that regulate maturation and cellular trafficking of ADAM17, we here perform overexpression studies of four ADAM17 variants located in the pro-, membrane-proximal- and cytoplasmic-domain of the ADAM17 protein in ADAM10/17-deficient HEK cells. Interestingly, we found a cancer-associated point mutation within the pro-domain of ADAM17 (R177C) to be most impaired in its proteolytic activity and trafficking to the cell membrane. By comparing this variant to an ADAM17 construct lacking the entire pro-domain, we discovered similar functional limitations and propose a crucial role of the pro-domain for ADAM17 maturation, cellular trafficking and thus proteolytic activity.
CRIS-Team Scopus Importer:2020-10-21
Keywords: ADAM17; Colon cancer; EGF-receptor; Metalloprotease; Secretory pathway; Shedding; Trafficking of membrane proteins; Tumor necrosis factor